Pariwisata dan Praktik Ilegal “Jaringan Tiongkok” di Bali - Zefanya S.D.I Picaulima; Hermini Susiatiningsih; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The increase in Bali tourism can be seen through the suffering of Chinese tourists in Bali in 2017. However, behind the domination of Chinese tourists in Bali, unknowingly there are illegal practices carried out by the